THE INFLUENCE OF FE-RICH COATINGS ON THE DISSOLUTION OF ANORTHITE AT PH 2.6 - Hodson M.E. (My University, 2003)
Surface coatings are very common on mineral grains in soils but most laboratory dissolution experiments are carried out on pristine, uncoated mineral grains. An experiment designed to unambiguously isolate the effect of surface coatings on mineral dissolution from any influence of solution saturation state is reported. Two aliquots of 53 to 63 μm anorthite feldspar powder were used. One was dissolved in pH 2.6 HCl, the other in pH 2.6 FeCl3 solution, both for ∼6000 h in flow-through reactors. An amorphous Fe-rich, Al-, Ca- and Si-free orange precipitate coated the anorthite dissolved in the FeCl3 solution. BET surface area of the anorthite increased from 0.16 to 1.65 m2 g−1 in the HCl experiment and to 3.89 m2 g−1 in the FeCl3 experiment. The increase in surface area in the HCl experiment was due to the formation of etch pits on the anorthite grain surface whilst the additional increase in the FeCl3 experiment was due to the micro- and meso-porous nature of the orange precipitate. This precipitate did not inhibit or slow the dissolution of the anorthite. Steady state dissolution rates for the anorthite dissolved in the HCl and FeCl3 were ∼2.5 and 3.2 × 10−10 molfeldspar m−2 s−1 respectively. These rates are not significantly different after the cumulative uncertainty of 17% in their value due to uncertainty in the inputs parameters used in their calculation is taken into account. Results from this experiment support previous theoretical and inference-based conclusions that porous coatings should not inhibit mineral dissolution.
Keywords: Anorthite